Localized buckling of the semi-infinite isotropic plate near elastically fastened edge - Reza Sharifian (National Academy of Sciences of Armenia)
Localized buckling of a semi-infinite isotropic plate near elastically fastened edge has been investigated. Mathematical model is of structure is provided and characteristic equation of the problem is derived. The existence conditions of localized buckling are derived analytically. For the cases when localized buckling exists numerical solutions and plots for the critical loads are provided.Рассмотрена задача о локализованной потере устойчивости полубесконечной пластинки-полосы, нагруженной по полубеслонечным шарнирно опертым краям и упруго опертой по конечному краю. Выведено характеристическое уравнение задачи и аналитически установлены условия существования локализованной неустойчивости. Получены также численные решения для критической нагрузки в зависимости от упругих характеристик пластинки и опоры. Դիտարկված է կիսանվերջ սալ-շերտի լոկալիզացված անկայունությունը, երբ երկու կիսանվերջ ազատ հենված եզրերում կիրառված է հավասարաչափ բաշխված բեռ, իսկ վերջավոր եզրը առաձգականորեն ամրակցված է: Ստացված է խնդրի բնութագրիչ հավասարումը և անալիտիկորեն դուրս են բերված լոկալիզացված անկայունության գոյության պայմանները: Կրիտիկական բեռի համար ստացված են թվային արժեքներ կախված սալի և հենարանի առաձգական գործակիցներից.
Keywords: Physics; Mechanics of deformable solids